Successful treatment by rituximab in a patient with TAFRO syndrome with cardiomyopathy - HIRAMATSU, Sumie; OHMURA, Koichiro; TSUJI, Hideaki; KAWABATA, Hiroshi; KITANO, Toshiyuki; SOGABE, Ayuko; HASHIMOTO, Motomu; MURAKAMI, Kosaku; IMURA, Yoshitaka; YUKAWA, Naoichiro; YOSHIFUJI, Hajime; FUJII, Takao; et al. (Nihon Rinshō Menʾeki Gakkai kaishi, 2016)
TAFRO syndrome is a newly defined disease entity which is characterized by thrombocytopenia, anasarca, myelofibrosis, renal dysfunction, and organomegaly. A histological pattern of multiple lymphadenopathy of atypical Castleman's disease (CD) is also an important characteristic. A 48-year-old man was referred to our hospital with fever, asthenia, bilateral pleural effusion, ascites, generalized edema, dyspnea, hypoalbuminemia, severe thrombocytopenia, anemia, renal failure and proteinuria, whereas bacterial culture and serological and PCR tests for various viruses were all negative. A CT scan showed multiple lymphadenopathy and tissue sampling of inguinal lymph nodes showed a compatible histology with plasma cell type CD. A diagnosis of TAFRO syndrome was made. Ten days after hospitalization, sudden cardiac insufficiency and anuria developed. Despite glucocorticoid pulse therapy, tocilizumab and plasmapheresis, clinical and laboratory features did not improve. On the 34(th) hospital day, we started rituximab. His general condition started to improve in several days, and by one month later anasarca had improved drastically. Thrombocytopenia and renal function gradually improved and finally normalized. Cardiac motion also improved. This is the first report of a TAFRO syndrome patient with cardiomyopathy, who was successfully treated with rituximab.